The importance of Kinesio Taping Therapy on the Complex Gait Recovery of Patients with Drop Foot after Stroke - Alexandra Ionela PRALA; Luminita Ionela GEORGESCU; Ion MIHAILA; Elena Ioana ICONARU; Stefan TOMA (Romanian Journal of Physical Therapy)
Introduction: Stroke causes peroneal nerve palsy manifested by weakness in dorsiflexion of the foot. This contributes to the respective gait impairment disrupting the swing phase of the gait cycle. Purpose: Through the proposed recovery program, we want to highlight the importance of using kinesio taping therapy in the specific recovery program to correct abnormal gait patterns in people with drop foot. Materials and Methods: In accordance with the strategy of gait recovery optimization in people with drop foot we conducted a longitudinal study over a period of 4 weeks with gait balance as test parameter. For the assessment of balance, we used the Berg Balance Scale and the Four Step Square Test, and the research group comprises a total of 10 subjects. The subjects were divided into two groups: the control group that received the classic recovery program and the experimental group that received the classic recovery program and the kinesio taping therapy. Results: According to the final evaluation results, the experimental group has made greater progress. Compared to the control group, the experimental group showed a progress rate of 18.2% higher. Results support the hypothesis that the use of kinesio taping helps to optimize gait recovery in people with drop foot after stroke. Conclusions: The correct alignment of the ankle joint during walking can be stimulated and maintained by the kinesio taping technique applied as complementary therapy, and the results obtained during assessing balance while gait support our conclusion.